2021
DOI: 10.1007/s13225-021-00475-9
|View full text |Cite|
|
Sign up to set email alerts
|

The evolving species concepts used for yeasts: from phenotypes and genomes to speciation networks

Abstract: Here we review how evolving species concepts have been applied to understand yeast diversity. Initially, a phenotypic species concept was utilized taking into consideration morphological aspects of colonies and cells, and growth profiles. Later the biological species concept was added, which applied data from mating experiments. Biophysical measurements of DNA similarity between isolates were an early measure that became more broadly applied with the advent of sequencing technology, leading to a sequence-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 243 publications
(337 reference statements)
0
57
0
Order By: Relevance
“…Hybridization processes in nature have also been repeatedly documented to occur between pairs of taxa within the H. annosum species complex (Garbelotto and Gonthier 2013;Sedlák and Tomšovský 2014;Sillo et al 2019). Both hybridization and genetic isolation happen in pathogenic yeasts of the genus Cryptococcus (Boekhout et al 2021). Some other studies have suggested hybridization to occur in other groups, for example Malassezia (Theelen et al 2004;Wu et al 2015) and other members of Ustilaginomycotina (Kellner et al 2011).…”
Section: Species Delimitation Criteria Commonly Used In Basidiomycotamentioning
confidence: 98%
See 2 more Smart Citations
“…Hybridization processes in nature have also been repeatedly documented to occur between pairs of taxa within the H. annosum species complex (Garbelotto and Gonthier 2013;Sedlák and Tomšovský 2014;Sillo et al 2019). Both hybridization and genetic isolation happen in pathogenic yeasts of the genus Cryptococcus (Boekhout et al 2021). Some other studies have suggested hybridization to occur in other groups, for example Malassezia (Theelen et al 2004;Wu et al 2015) and other members of Ustilaginomycotina (Kellner et al 2011).…”
Section: Species Delimitation Criteria Commonly Used In Basidiomycotamentioning
confidence: 98%
“…First, phenotypes may exhibit a variable extent of plasticity, which makes it untenable for this criterion to be used as the only one in species delimitation and recognition. Second, many fungal organisms, especially single-celled taxa such as the yeasts, typically display a limited set of taxonomically useful morphological characters, due to their relative simplicity (Boekhout et al 2021). In addition, their rate of morphological change is slower (Taylor et al 2006a, b).…”
Section: Species Delimitation Criteria Commonly Used In Basidiomycotamentioning
confidence: 99%
See 1 more Smart Citation
“…The Ustilaginomycotina includes mainly parasitic fungi and few of saprobic yeast or yeast-like members (Begerow et al, 2014). Traditionally, the phenotypic and ecological species concept with species identification based on the combination of host plants and morphological characteristics was applied for the plant pathogenetic fungi (Vánky, 2012;Begerow et al, 2014;Boekhout et al, 2021), but the integrative species concept with the incorporation of phenotypic and ecological characteristics and molecular data (e.g., rDNA and protein genes) have also been used (Stoll et al, 2003(Stoll et al, , 2005Begerow et al, 2006Begerow et al, , 2014Sipiczki and Kajdacsi, 2009;McTaggart et al, 2012a,b;Kijpornyongpan and Aime, 2017;Richter et al, 2019;Boekhout et al, 2021). For the yeast or yeast-like fungi, the molecular data, combined with morphological and physiological characters, was mainly used to identify species and diagnose genus (Kurtzman et al, 2011;Begerow et al, 2014Begerow et al, , 2017Richter et al, 2019;Boekhout et al, 2021).…”
Section: New Taxon Delineation and Phylogenetic Placementmentioning
confidence: 99%
“…Traditionally, the phenotypic and ecological species concept with species identification based on the combination of host plants and morphological characteristics was applied for the plant pathogenetic fungi (Vánky, 2012;Begerow et al, 2014;Boekhout et al, 2021), but the integrative species concept with the incorporation of phenotypic and ecological characteristics and molecular data (e.g., rDNA and protein genes) have also been used (Stoll et al, 2003(Stoll et al, , 2005Begerow et al, 2006Begerow et al, , 2014Sipiczki and Kajdacsi, 2009;McTaggart et al, 2012a,b;Kijpornyongpan and Aime, 2017;Richter et al, 2019;Boekhout et al, 2021). For the yeast or yeast-like fungi, the molecular data, combined with morphological and physiological characters, was mainly used to identify species and diagnose genus (Kurtzman et al, 2011;Begerow et al, 2014Begerow et al, , 2017Richter et al, 2019;Boekhout et al, 2021). Nearly 100 anamorphic yeast or yeast-like species in Ustilaginomycotina have been reported (Boekhout et al, 2003;Kurtzman et al, 2011;Begerow et al, 2014;Nasr et al, 2014;Albu et al, 2015;Wang et al, 2015;Sun et al, 2018;Richter et al, 2019), but only few of them have been connected to the sexual taxa or sexual stage, such as Pseudozyma prolifica (teleomorph My.…”
Section: New Taxon Delineation and Phylogenetic Placementmentioning
confidence: 99%